Ärztliche Einbestellungspflichten - Ahmadi, Milad (Schriften zum Gesundheitsrecht (SGR), 2021)
»Appointment and information duty of medical staff« Most medical treatments cannot be accomplished through a single medical appointment. In fact, treatments usually require multiple appointments across a defined timeframe. This results in temporal interruptions during treatment which can negatively impact the patient's health. This study highlights the duty of information that medical personnel have towards patients during temporal interruptions of treatments under German law. In addition, topics such as legal principles of the medical profession, the role of patient negligence and aspects of procedural legal are also discussed.